2017
DOI: 10.1097/md.0000000000007146
|View full text |Cite
|
Sign up to set email alerts
|

Association between formaldehyde exposure and miscarriage in Chinese women

Abstract: The aim of this study was to assess whether higher plasma formaldehyde concentration existed in women diagnosed with miscarriage and whether it contributed to higher risk of miscarriage in Chinese women.A case-control study was conducted in 118 women with a diagnosed miscarriage at the first trimester and 191 healthy women who delivered at term. Plasma levels of formaldehyde were measured by gas chromatography in conjunction with mass spectrometry after derivatization of the formaldehyde to the pentafluorophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As mentioned above, in the I/R injury model, the different efficacy of drugs to inhibit formaldehyde in male and female may provide a new strategy for clinical treatment with different genders 42,43 . In addition, an increase in formaldehyde concentration in the air may lead to an increase in CHD, 72 supporting the correlation between formaldehyde and heart development. Therefore, the detection of formaldehyde concentration in the air and pregnant women's plasma provide a reliable potential indicator for the timely diagnosis of abnormal foetal heart development.…”
Section: The Role Of Formaldehyde In the Diagnosis And Treatment Of Cardiovascular Diseases And Heart Developmentmentioning
confidence: 90%
See 1 more Smart Citation
“…As mentioned above, in the I/R injury model, the different efficacy of drugs to inhibit formaldehyde in male and female may provide a new strategy for clinical treatment with different genders 42,43 . In addition, an increase in formaldehyde concentration in the air may lead to an increase in CHD, 72 supporting the correlation between formaldehyde and heart development. Therefore, the detection of formaldehyde concentration in the air and pregnant women's plasma provide a reliable potential indicator for the timely diagnosis of abnormal foetal heart development.…”
Section: The Role Of Formaldehyde In the Diagnosis And Treatment Of Cardiovascular Diseases And Heart Developmentmentioning
confidence: 90%
“…A case‐control study in China found that 118 women diagnosed with miscarriage had significantly higher levels of formaldehyde in their plasma than 191 women who delivered at term 72 . Notably, the increase in plasma levels of formaldehyde served as a miscarriage‐independent risk factor and the increased formaldehyde content also increased the risk of miscarriage.…”
Section: Formaldehyde and Heart Developmentmentioning
confidence: 99%
“…A significant number of pregnant women appear to visit health facilities for emergency management of induced abortion (2). While those women with unwanted pregnancy and having an intention to stop at early weeks of gestation is one inevitable characteristic of this group, attendance following an intrauterine foetal death or viability failure, due to various causes, is frequently mentioned (3)(4)(5). Numerous studies indicate that using medications, especially mifepristone and misoprostol, is preferred over aspiration or curettage interventions for terminating a first trimester pregnancy (6,7) or evacuating an early pregnancy failure (8).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, those women with unwanted pregnancy and having an intention to stop at early weeks of gestation are one inevitable aspect of this group, attendance following an intrauterine fetal death or viability failure, due to various causes, is frequently mentioned [3][4][5].This review will consider articles which included pregnant women up to 12 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%